A new insight into the role of aryl hydrocarbon receptor (AhR) in the migration of glioblastoma by AhR-IL24 axis regulation. (September 2021) - Liu, Yiyun; Chen, Yangsheng; Sha, Rui; Li, Yunping; Xu, Tong; Hu, Xiaoxu; Xu, Li; Xie, Qunhui; Zhao, Bin
Graphical abstract: Highlights: AhR gene plays an important role in maintaining the migration ability of glioblastoma. TCDD and FICZ inhibit the migration of glioblastoma through AhR pathway. IL24 is a downstream gene of AhR pathway in glioblastoma cells. AhR agonists inhibit the migration of glioblastoma by up-regulated IL24 expression. Abstract: Cancer occurrence and development are closely related to the environment. Aryl hydrocarbon receptor (AhR) is an important receptor mediating the toxic effects of many environmental compounds, and is also involved in regulating tumor cell migration. Glioblastoma is the most malignant glioma and exhibits high motility, but the effects of AhR on the migration of glioblastoma are still unclear. We aimed to understand the role of AhR in the migration of this type of tumor cell and to explore the underlying molecular mechanism. In cultured human neuroblastoma cells (U87), we found that AhR overexpression or knockdown increased or suppressed the migration ability of U87 cells, respectively. Furthermore, inhibition of basal activation of the AhR pathway suppressed migration ability, suggesting a positive correlation between endogenous activity of the AhR pathway and cell migration. When the AhR pathway was activated by 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) or 6-formyl [3, 2-b] carbazole (FICZ), the migration of U87 cells was inhibited by inducing the expression of a tumor suppressor, IL24, which is a downstream responsive gene of AhR activation. Moreover, a similar AhR-IL24-dependent mechanism for migration inhibition of TCDD was documented in a breast cancer cell line and a lung cancer cell line. This study demonstrated that AhR plays important roles in regulating the migration of glioblastoma, and the induction of the AhR-IL24 axis mediates the inhibition of migration in response to TCDD or FICZ treatment.